Immunohistochemical detection of nerve growth factor and its receptors in the rat periodontal ligament during tooth movement - Hussin, Akbar Sham; Sampson, Wayne John; Dreyer, Craig William; Pierce, Angela Mary; Ferguson, Ian Andrew (Pergamon, 2009)
Objectives Nerve growth factor (NGF) and its receptors, p75 and tyrosine receptor kinase A (Trk A), have been shown to increase following trauma. The aims of this study were to examine changes in the detection of NGF and its receptors during orthodontic tooth movement in the rat, and the effects of anti-NGF on these changes. Design Orthodontic separators were placed between the right maxillary first and second molars of Sprague–Dawley rats which were equally divided into two groups. Animals from the second group were injected with anti-NGF. The left sides served as controls, and animals were sacrificed at 0, 3, 7 and 14 days. Results Results of immunohistochemical localisation for p75, Trk A, calcitonin gene-related peptide (CGRP) and NGF showed staining intensity increased at day 3, with a peak at day 7 and decreasing intensity at day 14. Anti-NGF injected animals showed reduced staining at all observation periods. Conclusion Data suggest that orthodontic injury induces NGF production, leading to sprouting and invasion by CGRP-positive nerve fibers and that injection of anti-NGF reduces NGF tissue levels and prevents innervation by CGRP-positive fibers.